Distribution and comparison of two morphological forms of water soldier (Stratiotes aloides L.): a case study on Lake Słosineckie Wielkie (Northwest Poland) - Toma, Cezary (Biodiversity: Research and Conservation, 2006)
The investigation was aimed at demonstrating differences between the floating forms of Stratiotes aloides L. and the submerged one. The following plant features of 40 specimens and 909 leaves were examined: width, length, sex, number of generative and vegetative organs, dry mass of whole plants and their organs, leaf apex angle, leaf width measured 3 cm from the base, 10 cm from the base and 10 cm from the top, leaf area, cellular wall thickness, number of vascular bundles and number of chloroplasts. The leaf area was determined with an image analyzer Met-Ilo 8. Leaf cells were examined with the use of a confocal and optical microscope. Water and bottom deposits from the places of specimens collection were analysed. The results confirm the occurrence of two morphological forms of S. aloides in Lake Słosineckie Wielkie as well as the morphological and anatomical differences between them.